Oxidative pentose phosphate pathway is required for T cell activation and antitumor immunity - Zihong Chen; Kellen L. Olszewski; Rolf-Peter Ryseck; Xincheng Xu; Jacob A. Boyer; Christian G. Peace; Yihui Shen; Caroline R. Bartman; Lydia Lynch; Joshua D. Rabinowitz (Proceedings of the National Academy of Sciences, 2025)
Glucose is catabolized by two major metabolic pathways, glycolysis and the oxidative pentose phosphate pathway (oxPPP). The oxPPP generates nicotinamide adenine dinucleotide phosphate (NADPH) at two steps, glucose-6-phosphate dehydrogenase (G6PD), the most common enzyme deficiency in humans, and 6-phosphogluconate dehydrogenase (PGD). Previous literature suggests that G6PD supports but PGD limits T cell–mediated immunity. Here, we use T cell–specific knockout mouse models to show that both enzymes are required for antitumor immunity and response to immunotherapy. PGD knockout depletes mature T cells systemically, while G6PD loss does not reduce basal T cell populations but results in apoptosis upon activation. Such apoptosis is not reversed by major downstream products of the oxPPP, including antioxidants, nucleosides, or fatty acids. Instead, T cells are partially rescued by removal of media cystine, whose reduction requires NADPH. G6PD loss induces an oxidative stress response that upregulates cystine import, which together with low NADPH leads to fatal disulfide stress. Overall, these results highlight an essential role for the oxidative pentose phosphate pathway in cystine homeostasis and T cell–mediated immunity.